Creating Space for Reflection: Meaning-Making Feedback in Instrumental/Vocal Lessons - Sandberg-Jurström, Ragnhild (Frontiers in Education, 2022)
In higher music education, problems have been reported regarding students’ lack of independence in one-to-one instrumental/vocal lessons, little space for reflection, and education based on a hierarchical master–apprentice tradition, regulating and restricting students’ opportunities to learn and reflect. This article concerns video-recorded feedback activities in one-to-one instrumental/vocal lessons in specialist music teacher education, paying special attention to the space offered for student self-reflection and independence. The data comprise video-recorded one-to-one instrumental/vocal lessons between students and teachers. A social semiotic perspective is used to study representations of feedback meaning-making in the interaction between students and teachers as well as the understandings and approaches related to traditions and norms in music education. The findings indicate that feedback is constructed through two contrasting discourses, resulting in various ways of realizing feedback related to reflection opportunities. The negotiating discourse emphasizes opportunities for student self-reflections, drawing on current institutional curricula and government requirements regarding reflection abilities. In contrast, the controlling discourse emphasizes constraints on such opportunities, connected to the hierarchical master–apprentice music tradition. The feedback approaches realizing these discourses are described in terms of space for conversation or exploration as well as a call for attention or re-creation, evident in all studied lessons. The discussion addresses some didactic issues regarding the findings.